2021
DOI: 10.3390/jcm10174029
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Phantom Limb Pain and Improved Proprioception through a TSR-Based Surgical Technique: A Case Series of Four Patients with Lower Limb Amputation

Abstract: Four patients underwent targeted sensory reinnervation (TSR), a surgical technique in which a defined skin area is first selectively denervated and then surgically reinnervated by another sensory nerve. In our case, either the area of the lateral femoral cutaneous nerve or the saphenous nerve was reinnervated by the sural nerve. Patients were then fitted with a special prosthetic device capable of transferring the sense of pressure from the sole of the prosthesis to the newly wired skin area. Pain reduction af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 41 publications
0
10
0
7
Order By: Relevance
“…Eine aktuelle Studie [14] berichtet über 4 Patienten, beideneninnerhalb eines Zeitraums von 5,5 Jahren rein sensible Nerventransfers vorgenommen wurden. Der Stumpf des N. suralis wurde in einem Fall auf den Endast des N. saphenus und in einem weiteren auf den N. cutaneus femoris lateralis koaptiert.…”
Section: » Der Nachweis Klinisch Relevanter Funktioneller Verbesserun...unclassified
“…Eine aktuelle Studie [14] berichtet über 4 Patienten, beideneninnerhalb eines Zeitraums von 5,5 Jahren rein sensible Nerventransfers vorgenommen wurden. Der Stumpf des N. suralis wurde in einem Fall auf den Endast des N. saphenus und in einem weiteren auf den N. cutaneus femoris lateralis koaptiert.…”
Section: » Der Nachweis Klinisch Relevanter Funktioneller Verbesserun...unclassified
“…The peripheral nervous system also appears to play a role in phantom limb pain [13] . Amputees frequently develop neuromas, abnormal bundles of nerve tissue, at the site of amputation which can be seen in 13%-32% of patients.…”
Section: Introductionmentioning
confidence: 99%
“…A study in 2005 reported that 60–80% of amputees suffer from PLP [ 2 ], and in a subsequent study in 2020 this was reported as 67–87% of amputees [ 3 ], although not with the same intensity or frequency of symptoms [ 4 ]. PLP after amputation occurs due to multifactorial mechanisms [ 5 ]. There are various predictive factors that influence the perception of pain, such as pre-amputation pain, location, sex and time of evolution, among others [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…PLP after amputation occurs due to multifactorial mechanisms [ 5 ]. There are various predictive factors that influence the perception of pain, such as pre-amputation pain, location, sex and time of evolution, among others [ 5 ]. In 72% of cases, it appears in the week following the amputation [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation